Analisis Dimensi Strategi Kompetitif dan Pemetaan Strategic Group Produsen Kendaraan Sport Utility Vehicle di Pasar Indonesia - Irfan Prarendra; Peggy Hariwan (Forum Manajemen Indonesia (FMI), 2014)
The purpose of this study is to analyze the dimensions of competitive strategy and strategic mapping group of vehicle manufacturers in the segment Sport Utility Vehicle. Since the government applied liberalization automotive policy in 1999, the automotive industry in Indonesia has improved significantly so that the competition increased. It can be seen from the increasing number of foreign brands that entered Indonesia’s market. National car sales continue to rise and break the number of 1.229.903 units in 2013. The segmentation of products in the automotive industry is based on the function of vehicles consisting of passenger cars, commercial cars, buses and trucks. In the segmentation passenger car, there are four sub-segmentation are sedans, multi-purpose vehicle (MPV), sport utility vehicle (SUV) and a city car. SUV type itself is currently being developed in which the number sold in October 2013 to as many as 57.446 units. As a relatively new segment, the characteristics of competition in the SUV market has not been thoroughly established as other types of vehicles. This study uses descriptive analysis to collect data from various sources so that the results of this study will provide a comprehensive overview of the dimensions of competitive strategy and strategic group mapping vehicle manufacturers Sport Utility Vehicle (SUV) in the Indonesian market. Keywords: Analysis of competitive strategy and dimensions stretgic groupmapping, Sport Utility Vehicle (SUV) segment